2009
DOI: 10.1016/j.jebo.2009.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Bargaining under incomplete information, fairness, and the hold-up problem

Abstract: In the hold-up problem incomplete contracts cause the proceeds of relation-specific investments to be allocated by ex-post bargaining. The present paper investigates the efficiency of incomplete contracts if individuals have heterogeneous preferences implying heterogeneous bargaining behavior and -equally important -preferences are private information. As the sunk investment costs can thus potentially signal preferences, they can influence beliefs and consequently bargaining outcomes. The necessities of signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Von Siemens [23] considers investment incentives in a hold-up problem, in which the returns to relationship-specific investments are allocated by bargaining amongst individuals with heterogeneous social preferences that are private information. The investments can signal preferences and, thereby, influence beliefs and bargaining behavior.…”
Section: Related Literaturementioning
confidence: 99%
“…Von Siemens [23] considers investment incentives in a hold-up problem, in which the returns to relationship-specific investments are allocated by bargaining amongst individuals with heterogeneous social preferences that are private information. The investments can signal preferences and, thereby, influence beliefs and bargaining behavior.…”
Section: Related Literaturementioning
confidence: 99%
“…It has been shown in experimental economics, as well as in the behavioral operation management literature, that people are not motivated exclusively by monetary payoffs-they have social preferences (see Cooper and Kagel 2015;Loch and Wu 2008;Katok and Pavlov 2013). A stream of theoretical works investigates social preferences, such as inequality aversion, in the context of the hold-up problem (Gantner et al 1998, Oosterbeek et al 1999Sonnemans et al 2001;von Siemens 2009). Dufwenberg et al (2013) argue that the patterns observed in the hold-up problem are explained by reciprocity.…”
Section: Behavioral Contributionmentioning
confidence: 99%
“…Several articles have studied the holdup problem from behavioral perspectives. These articles study agents’ incentives to make relation‐specific investments, focusing on the issues of communication between parties (Ellingsen and Johannesson ; Charness and Dufwenberg ), private information about alternative opportunities (Sloof ), heterogeneous fairness preferences (von Siemens ), the role of contracts (Hoppe and Schmitz ), and the possibility of vengeance (Dufwenberg, Smith, and Van Essen ).…”
Section: Relationship To the Literaturementioning
confidence: 99%